A Literature Review of the Economics of COVID-19 - Abel Brodeur; David Gray; Anik Islam; Suraiya Jabeen Bhuiyan (Global Labor Organization (GLO), 2020)
The goal of this piece is to survey the emerging and rapidly growing literature on the economic consequences of COVID-19 and governmental responses, and to synthetize the insights emerging from a very large number of studies. This survey (i) provides an overview of the data sets used to measure social distancing and COVID-19 cases and deaths; (ii) reviews the literature on the determinants of compliance and effectiveness of social distancing; (iii) summarizes the literature on the socio-economic consequences of COVID-19 and governmental interventions, focusing on labor, health, gender, discrimination and environmental aspects; and (iv) discusses policy proposals.
Keywords: E00; I15; I18; J20; 330; COVID-19; coronavirus; employment; lockdowns